Life after Trafficking: A gap in the UK’s modern slavery efforts - Roberts, Kate (Anti-Trafficking Review, 2018)
The Modern Slavery Act (2015) was a symbol of the UK’s commitment to combatting exploitation and human trafficking. Yet the Act offers little help to people who have been trafficked to, or in, the UK to recover and build a new life.